Republic of Croatia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This paper reviews the relationship between real GDP growth and domestic bank lending to the private sector in Croatia after the 2008 global financial crisis (GFC), drawing on a cross-country analysis of European countries. Croatia's recession was substantially longer compared to peers due to both domestic and external factors. Bank credit to the private sector was found to be important for economic growth, but less than often perceived, especially during a boom-bust cycle. Using empirical analysis, this paper confirms that the deleveraging of the private sector, particularly nonfinancial companies, was slow and contributed to Croatia's prolonged recession. When provisions of nonperforming loans (NPLs) improved and the uncertainty following the GFC receded, credit supply increased, while demand for credit hesitantly picked up with the strengthening of the recovery. The paper thus reinforces that NPLs and how they are handled as well as real growth are important determinants for credit. These findings are supported by the cross-country analysis and corroborated by other studies.